2015 개정 통합과학과 과학탐구실험 교육과정의 2차 년도 적용 현황 추이 분석 - 곽영순; Kwak, Youngsun (대한지구과학교육학회지, 2020)
The purpose of this study is to analyze the current status of the second year of application of Integrated Science and Science Laboratory Experiments, which are common courses of high school, and to explore suggestions for curriculum development in the future. To this end, the results of the survey of a total of 244 science-core and general high schools were compared with the survey result of 2018 school year. In addition, in-depth interviews were conducted with nine science teachers of the focus group to discuss the current state of curriculum implementation. According to the results, as in the first year, most of the Integrated Science courses were implemented in 6-8 units, and in most schools the number of teachers in charge of Integrated Science per class were 3-4. In the teacher's focus group interview, teachers insisted that Integrated Science requires integrated teaching approaches and is good for generating students' interest, but it is difficult to implement process-based assessment due to issues such as ensuring fairness of assessment. Most of Science Laboratory Experiments courses were implemented in two semesters, one unit per semester, and there was little link between Integrated Science and Science Laboratory Experiments because of the different teaching staff. The school life record entry method of Science Laboratory Experiments has been changed to criterion-based assessment starting in 2019, so students' satisfaction or flow of classes is much better than expected, and teachers can teach without burden. Based on the research results, ways to support the settlement of Integrated Science and Science Laboratory Experiments as common subjects, and ways to improve those subjects in the next curriculum revision were suggested. 본 연구는 2019년도에 적용 2년차를 맞이한 고등학교 과학과 공통과목인 통합과학과 과학탐구실험의 2차 년도 적용 현황을 분석하고 이를 토대로 향후 과학과 고등학교 교육과정 개발을 위한 제언을 도출하는 것을 목적으로 한다. 이를 위해 총244개의 과학중점고와 일반고를 대상으로 설문조사를 실시한 결과를 2018년도 1차 년도 조사결과와 양적으로 비교하였다. 또한 초점집단을 구성하는 9명의 과학교사들과 심층면담을 실시하여 2차 년도 적용현황에 대한 심층 답변을 논의하였다. 연구결과에 따르면, 1차 년도와 마찬가지로 적용 2년차에도 통합과학은 대부분 6~8단위로 운영하고 있었으며, 학급당 통합과학을 담당하는 교사는 3~4명이 대부분인 것으로 나타났다. 교사 초점집단 면담에서 현장교사들은 통합과학이 통합적 지도를 필요로 하며 학생의 흥미와 관심 유발에도 좋지만, 평가공정성 확보 등의 문제로 과정중심 평가 등을 구현하기는 어렵다고 주장하였다. 과학탐구실험의 경우 대부분 학기당 1단위로 2개 학기로 운영하고 있었으며, 가르치는 사람이 달라서 통합과학과 과학탐구실험을 거의 연계하지 않는 것으로 나타났다. 2019년도부터 과학탐구실험의 학교생활기록 기재 방식이 절대평가로 변경되어서 상대평가로 성적산출을 하지 않아도 되므로 학생들의 만족도나 수업의 흐름이 기대한 것보다 훨씬 좋고, 부담없이 가르칠 수 있다고 교사들은 말하였다. 연구결과를 토대로 과학과 공통과목인 통합과학과 과학탐구실험 교육과정 안착을 위한 지원방안, 차기 과학과 교육과정 개정에서 통합과학과 과학탐구실험 과목의 개선 방안 등을 제안하였다.